Engajamento de trabalhadores na implementação de chatbot para atendimento aos usuários de uma universidade - Rossato, Danúbia Miorando (2020)
The central theme of this dissertation is the engagement of workers, which be researched in the context of implementing a chatbot to serve users at a university. This theme has been intensively investigated with a quantitative approach, but studies with a qualitative approach are still restricted, mainly at the national level. Thus, the relevance of studies with this focus is pointed out and also that seek an understanding of engagement in a certain period of time, and involving specific activities. In view of the above, this study aims to answer the following research question: How does the engagement of workers in a project aimed at implementing a chatbot to serve users of a university located in Rio Grande do Sul appear? The general objective is to understand the engagement of workers in a project to implement chatbot to serve users at a university in Rio Grande do Sul. The specific objectives were: a) To describe the project to implement chatbot in the HEI; b) Identify the elements that make up work resources, personal resources and work demands involving the implementation of the chatbot; c) Identify the perception of workers regarding the results obtained in the process of implementing the chatbot in the researched location. d) Check the engagement of workers in the chatbot implementation project. This research is configured in a case study, of an exploratory and qualitative nature, carried out in an HEI, in which 6 professionals involved in the implementation of the chatbot participated, of which, five belonging to the HEI and one belonging to the company providing the chatbot. Data were collected through semi-structured interviews, focus groups and document analysis, which were organized with the support of NVivo®11 software, triangulated and analyzed using content analysis. The results emphasize the importance of work resources for the engagement of workers. We conclude that it is of fundamental importance the availability of resources, on the part of the company, which enable the performance of labor activities, in order to encourage the search for positive results on the part of workers. The results indicate contributions to the advancement of knowledge regarding the fluctuation of engagement in the same activity, in this case a technological innovation project, during a determined period of time and with different available resources, based on the context of an HEI. In addition to that, they demonstrate the importance of the organization and the GP area, to analyze the best resource strategies and work demands, in order to seek a balance to achieve positive results. It also makes possible notes for future research, such as mixed, quantitative and qualitative research, in addition to comparative studies aimed at addressing this theme.